Angyalok a Szentírásban - Erika KOVÁCS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2015)
Angels in the Holy Bible. The present study is concerned with angels, which topic is very interesting and various raising a lot of questions. Nonetheless, there are only a few people engaged with this topic and there are even nowadays a lot of unanswered questions. That’s why we tried to give an answer to the origin of the angels, to their name and description in the light of the Holy Bible and what kind of role they have in God’s work. The first part of the study investigates the etymology of the angels in the Old and New Testament. Later we are getting an answer relating to the origin of the angels, investigating in different parts in the Bible. Then we speak about the names and the description of the angels dispersing those illusions, which so many people think relating to their person or appearance.